Effects of a surfactant-based gel on acute and chronic paediatric wounds: a panel discussion and case series. (2nd June 2019) - Kirsner, Robert S.; Amaya, Rene; Bass, Kathryn.; Boyar, Vita; Ciprandi, Guido; Glat, Paul M.; Percival, Steven L.; Romanelli, Marco; Pittinger, Timothy P.
Abstract : On 20 November 2018, following the International Society for Paediatric Wound Care conference, a closed panel meeting took place in which the use of a surfactant-based gel (PluroGel (PMM), Medline Industries, Illinois, US) in paediatric wound care was discussed. The authors shared their experiences, thoughts, experimental data and clinical results. The panel identified the need for a product that can gently cleanse paediatric wounds and remove devitalised tissue without causing discomfort or skin reactions, as well as potentially promote healing. In adults, PMM has been shown to assist healing by hydrating the wound, controlling exudate and debriding non-viable tissue. Islands of neo-epithelium have also been reported to appear rapidly in different parts of the wound bed. No adverse effects on these proliferating cells have been observed. In vitro data suggest that PMM can remove biofilm, as well as potentially promote healing through cell salvage. The panel, therefore, set out to discuss their experiences of using PMM in the paediatric patients and to establish a consensus on the indications for its use and application in this population. This article will describe the main outcomes of that discussion and present case studies from paediatric patients with a variety of wound types, who were treated with PMM by members of the panel.